Forms of Muslim children's spirituality: a critical contribution to the didactics of Islamic religious education studies - Ulfat, Fahimah (Studies in critical pedagogy, theology, and spirituality, 2023)
"This empirical study on the relationship of Muslim children to God in Europe is fundamental for the scientific understanding of the development and formation of the faith in God of Muslim children. At the same time, the findings from this work are also highly relevant for the further development of modern Islamic religious education in a secular and highly individualised society. The aim of this book is to prepare young believers for their life in a religiously plural society, in which the individual relationship to God and the reflexivity of one's own religion are a decisive prerequisite for preventing radicalisation and moral rigidity"--